Die samestelling en gebruik van vraelyste in kerklike opnames met verwysings na die Ned Geref Kerk se Kerkspieël-vraelyste - Zaaiman, Johan (Stellenbosch Theological Journal, 2017)
The construction and usage of questionnaires in church surveys with references to the Dutch Reformed church’s ‘Kerkspieël’ questionnaires This article works from the premise that practical theology interprets the functioning of the church. Therefore, practical theologians should also be knowledgeable about empirical approaches to investigate these matters. Surveys are an important tool in empirical investigations and questionnaire construction forms an integral part of this process to ensure collection of quality information. However, questionnaire construction can be challenging since it involves human communication and interpretation that is fluid and unique by nature, but attempts to generate from it standardised and controlled responses. Therefore, the quality of each item in a questionnaire must be examined thoroughly. As an example, this article identifies certain flaws in the Dutch Reformed Church’s ‘Kerkspieël’ surveys. These entail the following: double barrelled, ambiguous, unclear, general, abstract and emotionally-related wording, timeframe in questions, leading questions, and assumed knowledge. In practical theological research, these deficiencies can serve as examples urging researchers to be more focused when aiming to develop quality surveys.